2017
DOI: 10.1002/ange.201705400
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting the Evolutionary Relationship between Malarial Parasites and Plants To Develop New Herbicides

Abstract: Herbicide resistance is driving aneed to develop new herbicides.T he evolutionary relationship between apicomplexan parasites,s uch as those causing malaria, and plants is close enough that many antimalarial drugs are herbicidal and so represent novel scaffolds for herbicide development. Using ac ompound library from the Medicines for Malaria Venture, the model plant Arabidopsis thaliana, and ap hysicochemical database of knownh erbicides,acompound was discovered that showed post-emergence herbicidal activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…We recently demonstrated that antimalarial drugs, including the antifolates pyrimethamine and cycloguanil, have herbicidal activity against the model plant A. thaliana (Corral et al ., ,b, ). Given that both pyrimethamine and cycloguanil are known to target the DHFR domain of Plasmodium DHFR‐TS, it is probable that their herbicidal effect is via plant DHFR‐TS inhibition.…”
Section: Introductionmentioning
confidence: 97%
“…We recently demonstrated that antimalarial drugs, including the antifolates pyrimethamine and cycloguanil, have herbicidal activity against the model plant A. thaliana (Corral et al ., ,b, ). Given that both pyrimethamine and cycloguanil are known to target the DHFR domain of Plasmodium DHFR‐TS, it is probable that their herbicidal effect is via plant DHFR‐TS inhibition.…”
Section: Introductionmentioning
confidence: 97%
“…14 the Malaria Box, that some of these lead compounds were also herbicidal, with one compound MMV006188 being active in soil and glasshouse studies, resulting in a new chemical scaffold for herbicidal development and a putative new mode of action. 15 We therefore explored a further portion of the Malaria Box and evaluated the materials as herbicidal-type compounds. If any hits were obtained that were useful these materials were put through a series of structural modifications, to gain insight into potency; the compound was also used in physiological assays to decipher a mode of action.…”
Section: Introductionmentioning
confidence: 99%
“…Novel molecular targets may be discovered through computational approaches using the sequences of all expressed genes available from transcriptomes and genomes. Additionally, candidate molecules from other crop protection or medical sectors with known targets could be evaluated against plant targets using complete proteomes available from weed genomes, as has been conducted for antimalarial drugs as candidate herbicides using Arabidopsis as a model …”
Section: Weed Genomics For Novel and Improved Weed Managementmentioning
confidence: 99%
“…Additionally, candidate molecules from other crop protection or medical sectors with known targets could be evaluated against plant targets using complete proteomes available from weed genomes, as has been conducted for antimalarial drugs as candidate herbicides using Arabidopsis as a model. 73,74 Potentially disruptive technologies such as RNAi and gene drive may provide new tools for weed management with facilitation by weed genomics. RNAi targets could function as herbicide synergists, and/or as stand-alone herbicides, depending on the efficiency of transcript silencing that can be achieved.…”
Section: New Targets For Weed Controlmentioning
confidence: 99%